Partisipasi Warga terhadap Sistem Informasi Desa - Fadjarini Sulistyowati; Candra Rusmala Dibyorin (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
The existence of village information service using technology is one of the villages effort to achieve transparency of information to various parties. The existence of information systems make citizens’ access to get information more widely and easily. The important thing in this system is about the participation of the villagers. This research was conducted in Terong village, Dlingo - Bantul with the assumption that the information system in this village is one of the applications which afforded by LSM Combine Resource Institute participatory. The method of the research uses a qualitative descriptive study. Target of the research is social life or society as a whole or a whole entity. A technique to obtain data is from observations, focus group discussions and interviews with informants who are considered to be related to the information system of the village. The data analysis are using interactive analysis model which developed by Miles and Hubermann. The result showed that: 1. Public participation to the existence of village information system started when the system is put in place. 2. The emergence of community participation due to the great synergy between village officials, LSM and communities. 3. Participation of community should be increased by controlling the presence of village information system for the public.